Cosmological clues : evidence for the big bang, dark matter and dark energy - Devereux, Carolyn (Boca Raton, FL : CRC Press, 2021)
"Did the Universe have a beginning? Will it have an end? Or has it always been the same, never changing? This is the subject of cosmology; the study of the Universe, and this book provides a perfect introduction to the subject for anyone that is interested in the wonders of our Universe"--
The evolution -- The reasoning -- The clues -- The theories -- The problems -- The testing -- The future.
OCLC-licensed vendor bibliographic record.
Keywords: Cosmology; SCIENCE / General; SCIENCE / Cosmology; SCIENCE / Astrophysics & Space Science